Hubungan Body Image dan Motivasi Dengan Kualitas Hidup Pasien Gagal Ginjal Kronis Yang Menjalani Terapi Hemodialisa di Klinik Esa Pemuda - Ahmad Afifi; Eka Rokhmiati Wahyu Purnamasari; Danur Jaya (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Body image disturbance is one of the problems that chronic kidney failure patients undergoing hemodialysis will experience due to changes in the function of the patient's body structure due to the effects of hemodialysis. Patients also feel embarrassed in front of their families and society due to the physical changes they experience. The quality of life of patients with chronic kidney failure is often disturbed. The aim of this research is the relationship between body image and motivation and the quality of life of chronic kidney failure patients undergoing hemodialysis therapy at the Esa Pemuda Clinic in 2023. The research method that will be used is an analytical research design with a correlational design. cross-sectional approach, a population of 94 respondents using proportional stratified random sampling technique and a sample size of 48 respondents. Using the non-parametric Rank Spearman Ro test. The results are 5. There is a relationship between body image and the quality of life of chronic kidney failure patients undergoing hemodialysis therapy at the Esa Pemuda Clinic, p-value 0.000 < 0.05 and there is a relationship between motivation and the quality of life of chronic kidney failure patients undergoing hemodialysis therapy at the Esa Pemuda Clinic 0.000 < 0.05. Conclusion: Body image and motivation can influence the quality of life of patients undergoing hemodialysis at the Esa Pemuda Clinic.